Characteristics and Complications of Tuberculous Meningitis Patients with Hydrochepalus Undergone Fluid Diversion in Dr. Hasan Sadikin General Hospital, Bandung - Adriani Lawrencia Novalia; Afiat Berbudi; Ahmad Faried; Heda Melinda Nataprawira (International Journal of Integrated Health Sciences, 2018)
Objective: To describe the clinical characteristics and complications observed in tuberculous meningitis (TBM) patients with hydrocephalus who had undergone fluid diversion management.Methods: This was a cross-sectional descriptive observational study involving 28 TBM patients with hydrocephalus aged 0–5 years who had undergone ventriculoperitoneal shunt or extraventricular drainage in the period of July 2011 to July 2016 in Dr. Hasan Sadikin General Hospital, Bandung. Age, gender, head circumferences, nutritional status, and classical characteristics such as sunset eye, frontal bossing, cracked pot sign, venectation as well as complications such as infection, phlebitis, and exposed shunt documented in the hospital medical records were analyzed.Result: The study discovered that infant group was predominant (21/28). Some of the patients had macrocephalus (7/28) and 18 had good nutrition status (18/28). There were 4 patients with frontal bossing characteristics (4/28) and almost none was found with others classic hydrocephalus characteristics. This study found no complication such as infection, phlebitis, and exposed shunt in TBM patients with hydrocephalus who had undergone fluid diversion therapy in Dr. Hasan Sadikin General Hospital, Bandung.Conclusion: One of the most dominan characteristics of TBM patients with hydrocephalus is frontal bossing. Tuberculous meningitis patients with hydrocephalus in our center did not show any fluid diversion-related complications such as infection, phlebitis, or exposed shunt.Keywords: Tuberculous meningitis, hydrocephalus, fluid diversion DOI: 10.15850/ijihs.v6n1.1048